The Technical Efficiency of Collective Irrigation Schemes in South-Eastern of Tunisia - Naceur, Mahdhi; Mongi, Sghaier (International Journal of Sustainable Development & World Policy, 2013)
The purpose of this paper is to asses the technical efficiency (TE) and proposes a measure for irrigation water efficiency (IE) based on the concept of input-specific technical efficiency for a sample of 46 irrigators inZeuss-Koutine region (South eastern Tunisia). In this paper, data envelopment analysis (DEA) is used to quantify TE and IE.A major finding of the study is that the irrigation systems are clearly inefficient. Under constants returns to scale (CRS) specification, the average technical efficiency of the sample was 71.75%. A similar pattern of scores was shown for IE; although in this case the average IE was even lower (49.9%) indicating that if farmers became more efficient using the technology currently available, the same level of output can be produced using the same level of other inputs but with, on average, 50.1% less water irrigation. In a second stage, critical determinants of sub-vector efficiency are determined using a Tobit model. Education level (EDU) and agricultural training (AGT) showed a significant impact on the subvector efficiency for water. Such information is valuable for extension services and policy makers since it can help guide policies towards increased efficiency.